1997
DOI: 10.1128/aem.63.12.4833-4838.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of pcpA and its role in pentachlorophenol degradation by Sphingomonas (Flavobacterium) chlorophenolica ATCC 39723

Abstract: Sphingomonas (Flavobacterium) chlorophenolica ATCC 39723 degrades pentachlorophenol (PCP) through a catabolic pathway encoded by multiple genes. One gene required for PCP degradation is pcpA, which encodes information for a 30-kDa polypeptide, PcpA, found in the periplasm of the bacterium. The biological role of PcpA has remained unknown. We disrupted pcpA by replacing it with a defective copy through homologous recombination. The pcpA recombinant, mutant strains accumulated 2,6-dichlorohydroquinone (2,6-DiCH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The mapping of several peptides onto the translated sequence of the pcpA gene leaves little doubt that the enzyme is encoded by this gene. This assignment is further supported by the recent report that a strain of S. chlorophenolica in which pcpA had been knocked out accumulates DCHQ when grown in the presence of PCP (41), suggesting that pcpA encodes the enzyme which converts DCHQ to the next compound in the pathway.…”
Section: Discussionsupporting
confidence: 60%
“…The mapping of several peptides onto the translated sequence of the pcpA gene leaves little doubt that the enzyme is encoded by this gene. This assignment is further supported by the recent report that a strain of S. chlorophenolica in which pcpA had been knocked out accumulates DCHQ when grown in the presence of PCP (41), suggesting that pcpA encodes the enzyme which converts DCHQ to the next compound in the pathway.…”
Section: Discussionsupporting
confidence: 60%
“…PcpA has been suggested to play an essential role in PCP degradation, especially in the conversion of 2,6‐DCHQ [8] in ATCC39723. However, there has been no direct evidence that PcpA converts 2,6‐DCHQ.…”
Section: Discussionmentioning
confidence: 99%
“…PCP is converted to tetrachlorohydroquinone (TeCHQ) by PCP 4‐monooxygenase encoded by the pcpB gene [3,4], and subsequently TeCHQ is reductively dechlorinated to trichlorohydroquinone (TrCHQ) and subsequently to 2,6‐dichlorohydroquinone (2,6‐DCHQ) by reductive dehalogenase, which is encoded by the pcpC gene [5–7]. The pathway beyond 2,6‐DCHQ is unknown, although PcpA has been proposed to be involved in the conversion of 2,6‐DCHQ, based on the accumulation of 2,6‐DCHQ by a pcpA mutant [8].…”
Section: Introductionmentioning
confidence: 99%
“…24) However, our findings demonstrated that the TC-FDM possessed by the bacteria plays an important role in the dechlorination of halogenated aromatic compounds. In addition, genes derived from bacteria involved in PCP dechlorination have only been identified in Gram-negative bacteria 25,26) ; Gram-positive bacteria, including the strain PD653, have a different dechlorination mechanism. However, this study led to the first discovery of novel PCP dechlorination genes (hcbB1B2B3) in Gram-positive bacteria.…”
Section: Novel Catabolic Genes Involved In Catalyzing the Dechlorination Of Hcb And Pcpmentioning
confidence: 99%